Multi-rate sampled-data control of a fly-by-wireless autonomous quadrotor helicopter - Ossa-Gomez, C.; Rodrigues, L. (2012 25th IEEE Canadian Conference on Electrical and Computer Engineering (CCECE), 2012)
This paper presents a novel approach for multirate sampled-data control of a fly-by-wireless autonomous quadrotor using three feedback loops for each axis: one loop for attitude, another for velocity and a third loop for position. A wireless networked controller is proposed that uses sensor data that is sampled at different rates in different nodes. Appropriate control actions are also computed at different rates. Furthermore, a new piecewise-affine (PWA) control strategy is proposed to improve the system's stability under sampling rates that are significantly lower than the ones required with more classical approaches. Simulations using a nonlinear model and experimental results show very smooth tracking of set-points at a very low sampling frequency, which was the main objective of the new technique.